KAJIAN YURIDIS PENERAPAN PEMBUKTIAN TERBALIK TINDAK PIDANA KORUPSI ( juridical study of reverse releases of corruption criminal actions) - Suyono, Yoyok Ucuk (Fakultas Hukum Universitas Gresik, 2019)
Internationally, corruption is recognized as a very complex, systematic and widespread problem. As a world problem, corruption is a trans national border crime, and given its complexity and negative effects, corruption is categorized as an extraordinary crime, so that extraordinary measures are also needed. (Extra ordinary measure) by implementing an inverse proof system. That is, a system of proof that is charged to the suspect or defendant.ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â On the basis of the foregoing, the problems that need to be addressed are: